Manajemen Pembinaan Prestasi Organisasi PSTI Kabupaten Batang pada Pekan Olahraga Provinsi XVI Jawa Tengah tahun 2023 - Risa Yulitania; Agus Raharjo (Indonesian Journal for Physical Education and Sport, 2024)
This research aims to analyze the development achievement of PSTI organization at batang regency on the XVI province sport games in Central Java 2023. This research focuses on management functions, namely planning, organizing, actuating and controlling. The research uses qualitative research with a descriptive approach. The research location is PSTI Batang Regency. The research subjects were administrators, coaches and athletes. Data collection uses observation, interviews and documentation methods. The instruments used are observation, interviews and documentation instruments. The data analysis model in this research is triangulation, using three components consisting of data reduction, data presentation, and drawing conclusions. The results of the research were that the development achievement of PSTI organization at batang regency on the XVI province sport games in Central Java 2023, which included planning and monitoring functions, had not been running well. Meanwhile, the organizing and mobilization functions have been running well.